Diverse heterocyclic scaffolds as dCTP pyrophosphatase 1 inhibitors. Part 1: Triazoles, triazolopyrimidines, triazinoindoles, quinoline hydrazones and arylpiperazines. Issue 16 (15th August 2017) - Llona-Minguez, Sabin; Häggblad, Maria; Martens, Ulf; Throup, Adam; Loseva, Olga; Jemth, Ann-Sofie; Lundgren, Bo; Scobie, Martin; Helleday, Thomas
Graphical abstract: Abstract: A high-throughput screening campaign using a commercial compound library (ChemBridge DiverSET) revealed diverse chemotypes as inhibitors of the human dCTP pyrophosphatase 1 (dCTPase). Triazole, triazolopyrimidine, triazinoindole, quinoline hydrazone and arylpiperazine hits were clustered, confirmed by IC50 determinations, and their preliminary structure-activity-relationships (SAR) and ligand efficiency scores are discussed in this letter.